Cardiac arrhythmias during acute exacerbations of chronic airflow limitation: effect of fall in plasma potassium concentration induced by nebulised beta 2-agonist therapy. Issue 765 (July 1989) - Lim, R.; Walshaw, M. J.; Saltissi, S.; Hind, C. R.
Abstract : The effect on cardiac rhythm of the fall in plasma potassium concentration induced by nebulised beta2-agonist therapy was studied in 20 patients admitted to hospital with an acute exacerbation of their reversible chronic airflow limitation. Arrhythmias considered serious or potentially life-threatening were recorded in 13 patients (65%). However, there was no significant increase in these arrhythmias in the hour following administration of nebulised beta2-agonist despite a significant fall in plasma potassium concentration during this period.